The Music Experiences and Attitudes of a First Cohort of Prelingually Deaf Adolescent and Young Adult Cochlear Implant Recipients - Gfeller, Kate; Driscoll, Virginia; Smith, Rachel See; Scheperle, Christina (Seminars in Hearing, 2012)
The purpose of this study was to examine the musical engagement (participation and attitude) of pediatric cochlear implant (CI) recipients who were implanted during early childhood and who have reached age 15 or older. A questionnaire was administered to a group of 31 prelingually deaf CI users who receive annual follow-up services and assessment in a clinical research center. The questionnaire was used to examine involvement in and attitudes toward music in school, the community, and in the home; social affiliation (hearing, deaf, both) and mode of communication (oral, manual, both) also were examined. Despite the technical limitations of CIs in transmitting pitch, melody, and tone quality, over two thirds of this sample described music as being important or very important in their lives. A high level of past and present familial involvement in music was associated with higher levels of current involvement and importance of music in the lives of adolescent and young adult CI users. Comparisons were noted with data from prior studies of persons with hearing loss who were non-CI users.
Keywords: Cochlear implants; adolescents; music enjoyment